The Effectiveness of Psychoeducational Support Groups for Women With Breast Cancer and Their Caregivers: A Mixed Methods Study - Cipolletta, Sabrina; Simonato, Camilla; Faccio, Elena (Frontiers in Psychology, 2019)
Background: Previous studies on the effectiveness of psychological interventions in oncology mainly used quantitative measures and no study was conducted with regard to both caregivers and patients. Aim: This study evaluates the effectiveness of psychoeducational support groups, both for women with breast cancer, and for their informal caregivers through the use of quantitative and qualitative measures. Methods: A longitudinal design was used comparing two psychoeducational support groups with other two groups in a standard care control condition. Participants were 28 women with a diagnosis of breast cancer in the care of a hospital in Northern Italy, and 21 family caregivers. The quantitative data were collected by Cognitive Behavioral Assessment for Outcome Evaluation (CBA-OE) and the qualitative data through the use of semi-structured interviews. Results: The statistical analysis showed a significant change attributable to the psychological intervention that proves the effectiveness of such an intervention in the patients’ and caregivers’ group. The qualitative analysis allowed us to interpret the behavioral and psychological profile emerging from CBA-OE, by considering the subjective experience of the treatment groups. The group experience offered affective, relational and informative support, and allowed participants to create a network and to feel understood and reassured. Conclusions: The results suggest the usefulness of psychoeducational support groups for women with breast cancer and for their caregivers. The value of this kind of intervention is not only at an individual level but also at a systems level, and family involvement ensures the best positive outcomes.